Towards a framework for a new research ecosystem - Roberto Savona; Andrea Modena; Lucia Alessi; Cristina Maria Alberini; Iacopo Baussano; Ranieri Guerra; Sergio Pecorelli; Guido Rasi; Paolo Daniele Siviero; Petros Dellaportas; Sean Khozin; Roger M. Stein (Humanities & Social Sciences Communications)
There is a substantial disconnect between theoretical recommendations for how much a nation should invest in science, innovation, and technology, and the practical challenges of implementing those investments. In this note, we identify four key challenges that must be addressed to foster an environment conducive to collaboration across organizations and governments, while ensuring commercial rewards for both investors and innovators.